Starch based antimicrobial food packaging film towards a sustainable environment. Issue 1 (December 2020) - Mallick, N; Pal, D; Soni, A B; Jhariya, D C; Singh, D
Abstract: Smart biodegradable packaging materials help restrict food-borne pathogens and reduce wastage of food items. Normally, food is packaged in plastic films, which are seldom reprocessed, which ultimately leads to an adverse impact on the environment. However, our ecosystem can be preserved by the use of biodegradable packaging materials. Deterioration of food caused by food-borne pathogens and microorganisms represent a severe problem. Therefore, a highly encouraging active packaging innovation is the antimicrobial packaging. Various active compounds can be incorporated in the packaging film to extend the shelf-life of packaged foods. The starch-based film is considered as a cost-effective material for antimicrobial packaging. Moreover, essential oils can be incorporated to enhance the antimicrobial effect, i.e., slow down food-borne pathogens. This paper systematically examines the impact of three essential oils (cloves, basil, and cinnamon) on biodegradable starch-based film's antimicrobial action. Three pathogenic microorganisms, namely; Staphylococcus aureus, Bacillus cereus, and Escherichia coli were are used for the assessment of antimicrobial properties. All the films containing different essential oils have shown a significant antimicrobial action against all the three microbes studied in this work.